Primary Health Care from the perception of women living in a rural area - Érica de Brito Pitilin; Maicon Henrique Lentsck (SciELO, 2015)
AbstractOBJECTIVEUnderstanding the perception of women living in a rural area about the actions and services of Primary Health Care (PHC) in a municipality of southern Brazil, which is the only one regarded as predominantly rural.METHODA descriptive study of qualitative approach, carried out with women who lived in the countryside and required health services in the 15 days prior to collection.RESULTSThe results registered low fidelity to PHC attributes, focusing its functional axis on sickness, transforming the unit into small points of emergency care and a bureaucratic place where patients are referred to other types of services. The quality of service offered is compromised to offering quick, fragmented and unequal treatment in the rural context.CONCLUSIONThe findings of this study highlight the need for greater efforts in order to adequate the new care model in the development of appropriate actions as designated by PHC in the rural context studied.